ASSOCIATION BETWEEN RECORD GYNECOLOGICAL-OBSTETRICS AND CLIMACTERIC SYMPTOMS - Estela Rodrigues Paiva Alves; Juliana Cristina Cruz Calazans; Almiranice Yara de Moura Ferreira; Gerlaine de Oliveira Leite; Khivia Kiss da Silva Barboza; Maria Djair Dias (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/2179769210567 Aim: to check the association between the gynecological-obstetric background and menopausal symptoms. Method: exploratory research, descriptive, cross-sectional of quantitative approach, involving 260 climateric women. We excluded women who were hormone replacement therapy, use hormonal contraceptives and phytoestrogens up to six months prior to collection. Was used for data collection two questionnaires, one with gynecological-obstetric data and the Blatt&Kupperman Menopausal Index. Data were analyzed using the techniques of descriptive and inferential statistics. Results: the mild symptoms were the most frequently reported by women, they were associated with those who also reported regular menstrual flow. Conclusion: the gynecological-obstetrical history may be related to the possible symptoms of menopause.